Global RNA recognition patterns of post‐transcriptional regulators Hfq and CsrA revealed by UV crosslinking in vivo. (4th April 2016) - Holmqvist, Erik; Wright, Patrick R; Li, Lei; Bischler, Thorsten; Barquist, Lars; Reinhardt, Richard; Backofen, Rolf; Vogel, Jörg
Abstract: The molecular roles of many RNA‐binding proteins in bacterial post‐transcriptional gene regulation are not well understood. Approaches combining in vivo UV crosslinking with RNA deep sequencing (CLIP‐seq) have begun to revolutionize the transcriptome‐wide mapping of eukaryotic RNA‐binding protein target sites. We have applied CLIP‐seq to chart the target landscape of two major bacterial post‐transcriptional regulators, Hfq and CsrA, in the model pathogen Salmonella Typhimurium. By detecting binding sites at single‐nucleotide resolution, we identify RNA preferences and structural constraints of Hfq and CsrA during their interactions with hundreds of cellular transcripts. This reveals 3′‐located Rho‐independent terminators as a universal motif involved in Hfq–RNA interactions. Additionally, Hfq preferentially binds 5′ to sRNA‐target sites in mRNAs, and 3′ to seed sequences in sRNAs, reflecting a simple logic in how Hfq facilitates sRNA–mRNA interactions. Importantly, global knowledge of Hfq sites significantly improves sRNA‐target predictions. CsrA binds AUGGA sequences in apical loops and targets many Salmonella virulence mRNAs. Overall, our generic CLIP‐seq approach will bring new insights into post‐transcriptional gene regulation by RNA‐binding proteins in diverse bacterial species. Synopsis: A new pipeline for CLIP‐seq in Salmonella maps global RNA–protein interactions and offers a tool for improved understanding of post‐transcriptional control in bacteria. Transcriptome‐wide mapping of Hfq and CsrA target sites by CLIP‐seq. Rho‐independent terminators comprise a general Hfq‐binding motif. Hfq binds 5′ to sRNA‐binding sites in mRNA targets and 3′ to seed sequences in cognate the sRNAs. CsrA preferentially recognizes AUGGA sequences present in loops of hairpin structures. CsrA binds and regulates many mRNAs encoding virulence factors. Abstract : A new pipeline for CLIP‐seq in Salmonella maps global RNA–protein interactions and offers a tool for improved understanding of post‐transcriptional control in bacteria.